Music, identity, and musical ethnocentrism of young people in six Asian, Latin American, and Western cultures. Issue 12 (29th October 2013) - Boer, Diana; Fischer, Ronald; González Atilano, Ma Luisa; de, Jimena; Moreno García, Luz Irene; Mendoza, Socorro; Gouveia, Valdiney V.; Lam, Jason; Lo, Eva
Abstract Ethnomusicologists and sociologists have extensively discussed the symbolic role of music in the creation, maintenance, and expression of cultural and national identity, while the underlying social psychological processes remain unexplored. We elaborate psychological mechanisms of identity construction and identity expression through culture‐specific music preferences. We propose and test a model linking music preferences to national identity via musical ethnocentrism in six student samples from Brazil, Germany, Hong Kong, Mexico, New Zealand, and the Philippines. In each context, culture‐specific music styles were related to national identity of its listeners and musical ethnocentrism mediated these effects. This paper bridges culture‐specific and universal perspectives on music and identity by examining the underlying psychological processes in Asian, Latin, and Western cultures.